2007
DOI: 10.1111/j.1365-294x.2007.03319.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic drift vs. natural selection in a long‐term small isolated population: major histocompatibility complex class II variation in the Gulf of California endemic porpoise (Phocoena sinus)

Abstract: Although many studies confirm long-term small isolated populations (e.g. island endemics) commonly sustain low neutral genetic variation as a result of genetic drift, it is less clear how selection on adaptive or detrimental genes interplay with random forces. We investigated sequence variation at two major histocompatibility complex (Mhc) class II loci on a porpoise endemic to the upper Gulf of California, México (Phocoena sinus, or vaquita). Its unique declining population is estimated around 500 individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 75 publications
2
31
1
1
Order By: Relevance
“…genetic drift). This was evidenced in some endangered species, such as vaquita [20]. However, it was surprisingly found in the present study that, contrary to the previous studies with neutral markers, the baiji showed considerable genetic variation at an adaptive MHC locus.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…genetic drift). This was evidenced in some endangered species, such as vaquita [20]. However, it was surprisingly found in the present study that, contrary to the previous studies with neutral markers, the baiji showed considerable genetic variation at an adaptive MHC locus.…”
Section: Discussioncontrasting
confidence: 83%
“…However, in small populations or endangered species, demographic effects such as population bottleneck and genetic drift usually resulted in limited MHC diversity and increasing species vulnerability of pathpgens and parasites [17][18]. This was evidenced in the Spanish ibex Capra pyrenaica [19], and Gulf of California endemic porpoise Phocoena sinus [20], although a link between the level of MHC variation and the condition of populations or species has not been convincingly demonstrated. On the other hand, other species such as island fox ( Urocyon littoralis ) [21] have maintained moderate to high MHC variability despite severe population bottleneck.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the endemic endangered Galápagos penguin Spheniscus mendiculus exhibited the lowest MHC diversity of eight penguin species studied (Bolmer et al 2007), while the endemic Seychelles warbler (Acrocephalus sechellensis) had reduced MHC diversity in comparison with the more cosmopolitan and migratory A. arundinaceus (Richardson and Westerdahl 2003). In Eurasian beaver (Castor fiber), seven relict populations were found monomorphic for DRB locus (Babik et al 2005), while one fixed DQB allele was detected in the unique declining population of the porpoise Phocoena sinus, endemic to the upper Gulf of California (Munguia-Vega et al 2007). …”
Section: Discussionmentioning
confidence: 95%
“…El golfo de California es una de las regiones en las cuales este enfoque ha sido más exitoso. Por ejemplo, se ha sugerido que la supervivencia de la única población de vaquita marina (Phocoena sinus Norris y McFarland, 1958) depende más de las actividades antropogénicas que de su diversidad genética, la cual es extremadamente baja (Munguia-Vega et al 2007). En especies comerciales, como la cabrilla sardinera, Mycteroperca rosacea (Streets, 1877), la información genética ha sido útil para diseñar zonas de no pesca en el norte del golfo de California, el cual alberga una alta diversidad genética y podría ayudar a que se recuperen zonas de pesca cercanas a través de la dispersión de larvas (Jackson et al 2015).…”
Section: Introductionunclassified
“…The Gulf of California is one of the areas in which this approach has been more successful. For example, it has been suggested that the survival of the only vaquita population (Phocoena sinus Norris and McFarland, 1958) depends more on human activities than on its genetic diversity, which is extremely low (Munguia-Vega et al 2007). In commercial species, such as the leopard grouper, Mycteroperca rosacea (Streets, 1877), genetic information has been used to design no-take zones in the upper Gulf of California, which hosts high genetic diversity and could replenish nearby fishing grounds due to larval dispersal (Jackson et al 2015).…”
Section: Introductionmentioning
confidence: 99%